Prove: a' + a(a'b + b'c)' = a' + b + c'

This is what I get so far for the LHS

a' + a(ab'bc') --> a' + ab'bc' .. So we know b'b is always 0 so does that mean we can just ignore it? ---> a' + ac' --> a' + c' .. but i am missing a b somewhere..

also problem 2:

(a'b' + c)(b+a)(b' + ac) = a'bc

my question is.. can you foil boolean algebra out like in regular algebra? like for this example can i do:

a'b'b + a'ab' + cb + ac ... etc? or no??

please advise! thanks

This is what I get so far for the LHS

a' + a(ab'bc') --> a' + ab'bc' .. So we know b'b is always 0 so does that mean we can just ignore it? ---> a' + ac' --> a' + c' .. but i am missing a b somewhere..

also problem 2:

(a'b' + c)(b+a)(b' + ac) = a'bc

my question is.. can you foil boolean algebra out like in regular algebra? like for this example can i do:

a'b'b + a'ab' + cb + ac ... etc? or no??

please advise! thanks

Last edited: